Modelling of Differential Evolution Based Automatic Generation Control for Two Area Interconnected Power Systems - Mishra, Saroj Kumar; Pati, Subhranshu Sekhar (Journal of Informatics and Mathematical Sciences, 2019)
This study demonstrates Automatic Generation Control (AGC) of Differential Evolution(DE) tuned two degree of freedom of proportional integral derivative (2DOF-PID) controller of a 2 area interrelated power structure. The 2 area based non reheat thermal power plant model is considered for the study and performance is compared with proposed controller over traditional controller configuration. The designed controller parameters are tuned through DE optimization algorithm in which objective function is formulated with help of ITAE function. Finally diverse loading condition (1%, 5% and 10% SLP) is applied in both areas to analyses the robustness of the proposed controller. The performance signifies the improved response with use of proposed controller over other controller.